2017
DOI: 10.1038/s41598-017-15910-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum steerability based on joint measurability

Abstract: Occupying a position between entanglement and Bell nonlocality, Einstein-Podolsky-Rosen (EPR) steering has attracted increasing attention in recent years. Many criteria have been proposed and experimentally implemented to characterize EPR-steering. Nevertheless, only a few results are available to quantify steerability using analytical results. In this work, we propose a method for quantifying the steerability in two-qubit quantum states in the two-setting EPR-steering scenario, using the connection between jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Such transformations can be represented by matrix multiplication in homogeneous coordinates, by a 3 × 3 invertible matrix H. That is, the projective point⃗ x is transformed to H⃗ x. If we begin with the conic in equation (33), after the transformation these points satisfy (H −1 ⃗ x) ⊤ A(H −1 ⃗ x) = 0. This means that the matrix defining the conic transforms as…”
Section: Projective Geometrymentioning
confidence: 99%
“…Such transformations can be represented by matrix multiplication in homogeneous coordinates, by a 3 × 3 invertible matrix H. That is, the projective point⃗ x is transformed to H⃗ x. If we begin with the conic in equation (33), after the transformation these points satisfy (H −1 ⃗ x) ⊤ A(H −1 ⃗ x) = 0. This means that the matrix defining the conic transforms as…”
Section: Projective Geometrymentioning
confidence: 99%
“…The definition of steering through informational properties, allows its analysis in theories involving quantum operators and quantum protocols, for instance by way of POVMs [96,185]. Even more, steering was proved completely equivalent to the capacity to carry out joint generalized measurements [186][187][188][189][190][191]; this means that the measurements that cannot be realized at the same time are the ones that reveal steering.…”
Section: Information Theorymentioning
confidence: 99%
“…In [189] a steering measure is found for the case of two-qubit, two-settings, from the correspondence of steering with joint measurability. In the sense of the distance to the unsteerable assemblages (see section 3.2.3.2), a class of steerable states is defined, for which upper and lower bounds are found that are related to the nonlocality given by maximal violation of the CHSH inequality.…”
Section: Other Informational Measuresmentioning
confidence: 99%
“…It should be noted that this steering criterion can be also derived from the result of Ref. [52]. However, our criteria from Theorem 1 and 2 do not need to know the detailed state.…”
mentioning
confidence: 95%